Assessing the association between on-field heading technique and head impact kinematics in a cohort of female youth soccer players - Filben, T. M.; Tomblin, B. T.; Pritchard, N. S.; Bullock, G. S., Hemmne, J. M.; Neri, K. E.; Krug, V.; Miles, C. M.; Stitzel, J. D.; Urban, J. E. (Science and Medicine in Football, 2024)
There is concern that exposure to soccer headers may be associated with neurological sequelae. Training proper heading technique represents a coachable intervention that may reduce head acceleration exposure. The objective was to assess relationships between heading technique and head kinematics in female youth soccer players. Fourteen players (mean age = 14.4 years) wore instrumented mouthpieces during practices and games. Headers were reviewed by three raters to assign a technique score. Mixed models and LASSO regression evaluated associations of technique with peak linear acceleration (PLA), rotational acceleration (PRA), rotational velocity (PRV), and head impact power ratio (HIP Ratio) while adjusting for session type and ball delivery. Two hundred eighty-nine headers (n = 212 standing, n = 77 jumping) were analyzed. Technique score (p = 0.043) and the technique score - session type interaction (p = 0.004) were associated with PRA of standing headers, whereby each 10-unit increase in technique score was associated with an 8.6% decrease in PRA during games but a 5.1% increase in PRA during practices. Technique was not significantly associated with any other kinematic metrics; however, peak kinematics tended to decrease as technique score increased. LASSO regression identified back extension and shoulder/hip alignment as important predictors of peak kinematics. Additional research on heading technique and head acceleration is recommended.